Silicone-based fire protection sheet, method for producing same, and battery pack having same

By using silicone-based fireproof sheets in the battery pack, the high load amount of thermal insulation filler is bonded to the silicone polymer adhesive, and the problems of thermal runaway propagation and working environment pollution in the battery pack are solved, achieving good thermal protection and mechanical properties.

CN119856324APending Publication Date: 2025-04-18DOW SILICONES CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202280099899.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-09-16
Publication Date
2025-04-18

Smart Images

  • Figure BDA0005303759390000191
    Figure BDA0005303759390000191
  • Figure BDA0005303759390000201
    Figure BDA0005303759390000201
  • Figure BDA0005303759390000202
    Figure BDA0005303759390000202
Patent Text Reader

Abstract

The present disclosure provides a silicone-based fire protection sheet, a method of producing the same, and a battery pack having the same. The present invention relates to a silicone-based fire-proof sheet having a structure in which at least one thermally insulating filler selected from aerogel particles, hollow particles and mesoporous particles is bonded in a silicone-based polymer binder, in which when the total mass of the solid content of the silicone-based fire-proof sheet is 100 mass%, the total mass of the solid content of the silicone-based fire-proof sheet is 100 mass%, the total mass of the solid content of the silicone-based fire-proof sheet is 100 mass%, and the total mass of the solid content of the silicone-based fire-proof sheet is 100 mass%. The amount of the thermal insulation filler ranges from 5% by mass to 40% by mass, and the amount of the silicone-based polymer binder ranges from 57.5% by mass to 95% by mass.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a silicone-based fireproof sheet, a production method thereof, and a battery pack having the sheet; to the use of the silicone-based fireproof sheet in a battery pack; and to a method for producing a battery pack using the silicone-based fireproof sheet. Background Art

[0002] In order to control the carbon dioxide emissions to the atmosphere and to curb global warming from the greenhouse gas effect, the production of electric vehicles (EVs) powered by rechargeable lithium-ion batteries (LIBs) has begun to surge in major geographical regions around the world. In order to increase the mileage per charge, EV battery manufacturing targets battery cathode and anode materials with higher energy density. At the same time, due to the use of nickel-based lithium metal oxides with higher Ni%, the risk of triggering thermal runaway propagation increases with higher energy density. In order to control the risk of thermal runaway propagation in battery packs with prismatic or pouch-shaped cells, as a typical passive strategy, a thermal insulation sheet is placed between two adjacent individual battery cells. Once thermal runaway occurs on a cell (the so-called ignited cell), the temperature inside the cell will quickly increase to 400°C or above, such as 600°C, 800°C, or even 1000°C. As a result, the surface of the cell becomes hot, with a temperature exceeding 350°C or above, such as 550°C, 750°C, or 950°C. The thermal insulation sheet can delay heat transfer from the hot surface of the ignited cell to the adjacent good cell. The typical thermal insulation sheet adopted by the industry is an aerogel sheet with aerogel powder compacted in a fabric mat. The aerogel powder can ensure thermal insulation performance, and the fabric mat holds the powder together in a sheet shape. However, due to its inherent low density and poor van der Waals forces between particles, the aerogel powder on the surface of the sheet can easily diffuse into the atmosphere during processing. This leads to pollution of the working environment. How to develop a fireproof sheet with good thermal insulation performance and a clean working environment for the battery assembly process is a strong demand in the EV battery industry.

[0003] Silicone rubber can be ceramicized at a temperature that triggers its decomposition and condensation reaction. By adding a thermal insulation filler (e.g., aerogel powder or hollow glass beads) to a liquid silicone rubber, then curing and / or foaming it, the resulting sheet has silicone rubber as a matrix and a thermal insulation filler dispersed in the silicone rubber. When a unit undergoes thermal runaway, the silicone matrix in the adjacent sheet can undergo ceramicization, changing from soft rubber to rigid inorganic ceramics. In theory, the sheet after ceramicization can delay the thermal diffusion from the ignited unit to the adjacent good unit. On the other hand, since the thermal insulation filler is well bonded by silicone rubber, the sheet will not cause air pollution in the working environment. However, loading too much thermal insulation filler in liquid silicone rubber will result in too high viscosity and be unsuitable for coating process. The pad or sheet manufacturing in mass production defines the upper limit of the volume loading of fillers in liquid silicone rubber. Within this limit, the thermal insulation performance of the final sheet may not be enough to prevent thermal runaway propagation. How to develop a fireproof sheet with silicone rubber to bond the thermal insulation filler of sufficient loading together remains a challenge.

[0004] The present invention discloses a silicone-based fireproof sheet for battery packs to effectively prevent thermal runaway from propagating from a burning cell to adjacent cells. The sheet uses silicone to bond thermal insulation fillers, such as aerogel powder, wherein the content of the thermal insulation filler is 5% to 40% by mass, and the silicone content is >10% by mass, or the polymer binder content is >50% by mass. The following is a more detailed overview of the related prior art found. No prior art discloses a battery pack in which a silicone-bonded aerogel sheet is used, particularly a sheet having an aerogel particle content of 5% to 40% by mass and a silicone content of >10% by mass or a polymer binder content of >50% by mass.

[0005] CN108793932A claims a thermal insulation energy-saving material and a preparation method thereof, which is composed of the following raw materials in parts by weight: 30 to 60 parts of silica aerogel, liquid resin, 10 to 30 parts of modified vitrified microbeads, 30 to 50 parts of closed expanded perlite, 10 to 20 parts of lightweight aggregate, 8 to 15 parts of high viscosity clay, 2 to 8 parts of volcanic ash, 15 to 35 parts of inorganic fiber, 2 to 10 parts of dimethyl silicone oil, 1 to 5 parts of water glass, 2 to 6 parts of liquid resin, 0.5 to 1.5 parts of dispersant and 40 to 60 parts of deionized water. The material of the present invention has low thermal conductivity and low water absorption. In the preparation method, it is claimed that the water is first heated to 200°C, the liquid resin and silicone oil are placed in the heated water, and the liquid resin is dissolved in the water, and then the filler is added to form a slurry. Unlike the prior art, the present invention claims >50wt% of polymer binder in the dry sheet to ensure mechanical strength. By calculation, the maximum resin loading in the dry material in the prior art is 6 / (30+10+30+10+8+2+6+0.5)=6 / 96.5=6.2wt%. Obviously, the material claimed in the prior art cannot be used for thermal runaway propagation prevention sheets in batteries. In addition, the prior art claims a process of dissolving a liquid resin in hot water before adding a filler, and such a liquid resin should not be a silicone polymer because silicone polymers are insoluble in water.

[0006] US10604642B2 claims a solid thermal insulation material substantially free of phyllosilicates, comprising (a) 70% to 98% by volume of hydrophobic silica aerogel particles having an intrinsic density between 110 kg / m and 210 kg / m, (b) 0.3% to 12% by volume of an organic binder formed by at least one organic polymer (b1) and at least one surfactant (b2) or by an amphiphilic organic polymer (b3), these volume fractions being determined by image analysis of thin sections of the solid material and given relative to the total volume of the material, the aerogel particles having a particle size distribution with at least two maxima, wherein the first maximum corresponds to an equivalent diameter (d) of less than 200 μm, preferably between 25 μm and 150 μm, and the second maximum corresponds to an equivalent diameter (D) of between 400 μm and 10 mm, preferably between 500 μm and 5 mm. The prior art does not specify an organic binder as a silicone polymer. It teaches water-soluble or dispersible polymers, such as acrylic polymers or cellulose polymers, which cannot withstand the high temperatures that occur in battery thermal runaway. Unlike the prior art, the present invention discloses silicone polymers as the majority of the polymer binder, which ensures that the thermal runaway propagation in the battery pack is prevented. The silicone polymer in the binder should be >50wt%, preferably >60wt%, more preferably >70wt%. In some embodiments of the present invention, the volume % of the thermal insulating filler is less than 60%. In addition, the present invention does not require aerogel particles having a particle size distribution that exhibits at least two maxima.

[0007] US20070238008A1 claims an aerogel-based thermal management system and method for a vehicle that incorporates an aerogel material to provide insulation and thermal shielding. The aerogel material may be encapsulated in an encapsulating material such as a polymer, elastomer, or metal. Unlike the prior art, the present invention discloses a technique for using a silicone emulsion to bond thermally insulating fillers (e.g., aerogel powder), thereby eliminating the need for a housing or encapsulating material.

[0008] US10501597B2 discloses a silicone rubber composite foam comprising a silicone rubber adhesive and hollow glass beads, and the silicone rubber composite foam partially or completely fills the open space of the battery module housing and / or partially or completely covers the battery cells and / or partially or completely covers the module housing, and optionally covers the cover of the battery module housing. Unlike the prior art, the present invention discloses a sheet having a thermal insulation filler with a mesoporous structure or a hollow structure of >15wt%. It is not limited to hollow glass beads, so the sheet is not necessarily a silicone rubber composite foam. In addition, the present invention claims protection for a silicone emulsion for mixing with the filler and bonding the filler together in the final dry sheet. It was found that the silicone emulsion was necessary to meet the processability requirements.

[0009] EP3743466B1 claims a composition comprising an adhesive and a hydrophilic powder and / or gel, the adhesive comprising one or more silicone polymers, silicone resins, silicone-based elastomers and mixtures thereof, the hydrophilic powder and / or gel being selected from one or more amorphous porous hydrophilic silica, wherein the adhesive is a solution, emulsion or dispersion in water. Unlike the prior art, the present invention discloses a silicone sheet particularly useful for preventing the propagation of thermal runaway in a battery pack. The silicone sheet in the present invention comprises a thermal insulating filler not limited to porous hydrophilic silica. The thermal insulating filler may be one or a combination selected from porous hydrophobic silica, hollow inorganic balls, and the like. Porous hydrophobic silica and hollow glass beads are both listed in the comparative examples of the prior art. In addition, the prior art does not mention the final thermal insulation performance of the composition. The present invention claims that the final thermal insulation performance of the silicone sheet should meet specific acceptance criteria, which define the content of thermal insulating fillers and silicone polymers in the total adhesive.

[0010] Related technical literature

[0011] 1.CN108793932A

[0012] 2.US10604642B2

[0013] 3.US20070238008A1

[0014] 4.US10501597B2

[0015] 5.EP3743466B1 Summary of the invention

[0016] Problems to be solved by the present invention

[0017] The problem to be solved by the present invention is how to better utilize thermal insulating fillers such as aerogels in battery packs to prevent the propagation of battery thermal runaway without the working environment pollution problems of aerogel covers currently available on the market. The concept of the present invention is a sheet (mat) of silicone polymer-bonded thermal insulating fillers (such as aerogel particles) with a sufficiently high filler loading for use in battery packs. The sheet also contains sufficient silicone binder so that the sheet is non-flammable and has good mechanical properties for handling.

[0018] Methods used to solve problems

[0019] As a result of careful studies, the inventors have arrived at the present invention by finding that the above-mentioned problems can be solved by a silicone-based fire-proof sheet, which has a structure in which at least one thermally insulating filler selected from aerogel particles, hollow particles and mesoporous particles is bonded in a silicone-based polymer binder, wherein when the total mass of the solid content of the silicone-based fire-proof sheet is 100 mass%, the amount of the thermally insulating filler ranges from 5 mass% to 40 mass%, and the amount of the silicone-based polymer binder ranges from 57.5 mass% to 95 mass%.

[0020] In the above-mentioned silicone-based fireproof sheet, the average size or diameter of the thermal insulation filler is not particularly limited, but generally ranges from 1 μm to 1.20 mm, and at least 50% by mass of the silicone-based polymer adhesive is a cured silicone product. In some embodiments of the present disclosure, when the total mass of the solid content of the silicone-based fireproof sheet is 100% by mass, the average size of the aerogel particles ranges from 0.01 mm to 1.0 mm, and the amount of the aerogel particles ranges from 15% to 35% by mass. In some embodiments of the present disclosure, the silicone-based polymer adhesive is a water-based silicone polymer adhesive. In some embodiments of the present disclosure, the silicone-based polymer adhesive comprises a water-based silicone polymer adhesive, which comprises colloidal silica by a condensation curing reaction using alkoxysilane as a crosslinking agent. In some embodiments of the present disclosure, the silicone-based polymer adhesive further comprises at least one selected from the group consisting of: a flame retardant additive, a curing catalyst, a rheology modifier, a defoaming additive, a wetting additive, a surface treatment agent, a colorant, a filler different from the thermal insulation filler, an antioxidant additive, a biocide, an ultraviolet (UV) stabilizer additive, a biocide, and an adhesion promoter additive. In some embodiments of the present disclosure, the silicone-based fireproof sheet can be applied to a battery pack.

[0021] In addition, the present disclosure provides a battery pack structure, wherein the silicone-based fireproof sheet is completely or partially arranged in the space between at least two adjacent individual battery cells. In some embodiments of the present disclosure, the battery is prismatic or pouch-shaped.

[0022] In the above-mentioned battery pack structure, the silicone-based fireproof sheet is a silicone-based product sheet that is cured before being arranged in the space between at least two adjacent individual battery cells. In some embodiments of the present disclosure, the silicone-based fireproof sheet is a silicone-based product cured by a curing reaction of a curable silicone-based composition in the space between at least two adjacent individual battery cells. The preferred shape of the battery cell is a prismatic or pouch shape, and the battery cell is preferably protected by the silicone-based fireproof sheet.

[0023] In addition, the present disclosure provides an aqueous curable silicone-based composition, which forms the silicone-based fire-proof sheet through a curing reaction, and the aqueous curable silicone-based composition comprises:

[0024] (A) a curable silicone-based polymer adhesive, which contains at least 50% by mass of a curable silicone polymer when the total mass of the solid content of the silicone-based fire-proof sheet is 100% by mass, and the amount of the curable silicone-based polymer adhesive ranges from 57.5% by mass to 95% by mass,

[0025] (B) at least one thermally insulating filler selected from aerogels and hollow particles, when the total mass of the solid content of the silicone-based fireproof sheet is 100 mass %,

[0026] The amount of the at least one thermally insulating filler ranges from 5% to 40% by mass,

[0027] (C) a curing agent of component (A),

[0028] (D) water, and optionally

[0029] (E) when the total mass of the solid content of the silicone-based fireproof sheet is 100 mass %, at least one selected from the group consisting of: flame retardant additives, curing catalysts, rheology modifiers, defoaming additives, wetting additives, surface treatment agents, colorants, fillers other than the thermal insulation filler, antioxidant additives, biocides, ultraviolet (UV)

[0030] Stabilizer additives and adhesion promoter additives.

[0031] In the above-mentioned aqueous curable silicone-based composition, component (A) is a silicone-based polymer binder containing curable silicone and other curable polymerizable materials in a mass ratio of 50:50 to 100:00. In some embodiments of the present disclosure, component (A) of the silicone-based polymer binder is emulsified or uniformly dispersed in (D) water.

[0032] In addition, the present disclosure provides a method for producing the silicone-based fire-proof sheet, the method comprising the following steps:

[0033] Step (I): a step of applying the aqueous curable silicone-based composition as a wet slurry layer onto a substrate, the substrate optionally having a release layer thereof to the coating, and

[0034] Step (II): a step of forming the silicone-based fire-proof sheet by removing water from the coated aqueous curable silicone-based composition at a temperature of up to 140° C. after the step (I).

[0035] In some embodiments of the present disclosure, in the step (I), the thickness of the wet slurry layer of the aqueous curable silicone-based composition ranges from 0.2 mm to 10.0 mm. The method for producing the silicone-based fire retardant sheet further comprises a step of controlling the viscosity and / or fluidity of the aqueous curable silicone-based composition by adding water and / or a rheology modifier before or simultaneously with the step (I).

[0036] In addition, the present invention provides a method for producing the battery pack structure according to claim 8, the method comprising the following steps:

[0037] Step (BI): a step of completely or partially filling the space between at least two adjacent individual battery cells with an aqueous curable silicone-based composition as a wet slurry layer, and

[0038] Step (B-II): After step (BI), a step of forming a silicone-based fire-retardant sheet in the space between at least two adjacent individual battery cells by removing water from the coated aqueous curable silicone-based composition at a temperature of up to 140°C.

[0039] Effects of the Invention

[0040] The present invention enables the production of silicone-based fireproof sheets that allow the addition of thermally insulating fillers at loadings of >15% by mass or more; and produce a cross-linked polysiloxane backbone as a binder matrix in the final sheet. Additionally, silicone-bonded thermally insulating sheets can be placed in battery packs to isolate hot spots or cells on fire and prevent / slow the spread of heat into surrounding areas or cells.

[0041] It is to be understood that both the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the invention, as claimed. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 is a schematic diagram of an apparatus for testing the thermal insulation performance of a silicone-based fireproof sheet according to the present disclosure.

[0043] Figure 2 1 are the background temperature curves of Examples IE-1 to IE-3 and Comparative Example CE1 in the present disclosure, wherein these curves are the background temperature curves of CE1, IE 1, IE 2 and IE 3 from top to bottom, respectively.

[0044] Figure 3 is the background temperature curve of Comparative Example CE 2 in the present disclosure.

[0045] Figure 4 ] are the background temperature curves of Example IE 4 and Example IE 5 in the present disclosure, wherein these curves are the background temperature curves of IE 4 and IE 5 from top to bottom, respectively. DETAILED DESCRIPTION

[0046] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs. As disclosed herein, "and / or" means "and, or as an alternative" or "in addition or alternatively". Unless otherwise indicated, all ranges are inclusive.

[0047] All phrases containing parentheses indicate either or both the inclusion of the parenthesized material and its absence. For example, the phrase "(aqueous) polyurethane" includes, in the alternative, polyurethane and aqueous polyurethane.

[0048] As used herein, the term "sheet" or "sheet form" means a flat product in the form of a mat or sheet having a thickness. Generally, "sheet" or "sheet form" includes mat forms, sheet forms, and other flat form products having various thicknesses.

[0049] As used herein, the term "thickness" refers to the average of at least three measurements of a dry sheet (eg, a sheet having a thickness of 0.8 mm to 1.2 mm) measured using an Ames Gage, Model 13C-B2600 (Ames Corporation Waltham MA).

[0050] As used herein, the terms "aerogel" and "aerogel material" describe a class of structures having low density, open pore structure, large surface area, and nanometer-scale pore size. Aerogel materials can be provided in at least powder, particles, beads, and other suitable forms, and include inorganic, organic, and hybrid organic-inorganic compositions, or some combination of the above forms and / or compositions.

[0051] In this context, the term "aerogel" means in the context of the present invention a gel obtained in a known manner by the sol-gel route, which gel has been dried. The term encompasses both appropriate aerogels obtained by supercritical drying of the gel formed and gels generally known as "xerogels" obtained by evaporative drying at atmospheric pressure. When considering large-scale production of the material of the present invention, xerogels are very advantageous due to their low cost, whereas aerogels exhibit more advantageous technical properties, but have high production costs.

[0052] The term "true density" is a quotient obtained by dividing the mass of a sample (such as the mass of glass bubbles) by the true volume of that mass of glass bubbles measured by a gas densimeter. The "true volume" is the aggregated total volume of the glass bubbles, not the loose volume.

[0053] As used herein, the term "polymer" or "polymerization" in the alternative refers to a polymer prepared from one or more different monomers, such as a copolymer, terpolymer, tetrapolymer, pentapolymer, etc., and can be any of a random polymer, a block polymer, a grafted polymer, a sequential polymer, or a gradient polymer.

[0054] As used herein, the term "solids" or "solids content" refers to any and every material in the composition other than water and solvent, if any.

[0055] As used herein, unless otherwise indicated, the term "average diameter" or "average size" means the weight or volume average diameter determined by light scattering (LS) using a BI-90 Particle Size Analyzer (Brookhaven Instruments Corp. Holtsville, NY), or the weight or volume average length of irregularly shaped particles measured by image analysis of images captured by any instrument such as SEM, TEM or optical microscope.

[0056] As used herein, the phrase "mass %" means mass percentage or % by mass and the phrase "wt. %" means weight percentage or wt %.

[0057] In order to effectively prevent the propagation of thermal runaway in the battery pack, it is highly preferred that there is a thermally insulating inorganic filler of>15% by mass or more in the silicone-based fireproof sheet. In the present disclosure, a silicone-based polymer binder (emulsion) allows the addition of a higher loading (e.g.,>15% by mass or more) of thermally insulating fillers in a silicone-based fireproof sheet. Liquid silicone rubber and resin and solutions of silicone rubber and resin in organic solvents are candidates for dispersing aerogel particles, followed by a drying and / or curing process to make silicone-bonded aerogel sheets. During the sheet manufacturing process, the organic solvent in the silicone polymer or resin solution needs to be accommodated by special equipment. When using liquid silicone rubber or resin, in some cases, and especially when the aerogel particle loading level is very high, the viscosity of the mixture can be high. Due to the high viscosity, it is extremely difficult to process such a high loading of thermally insulating fillers in such a liquid silicone rubber or resin. By using a silicone-based polymer binder emulsion, the viscosity of the wet slurry obtained after mixing the silicone-based polymer binder emulsion with the thermal insulation filler can be more easily tuned to meet the processability requirements. In addition, by using a silicone-based polymer as a majority of the polymer binder, it produces a cross-linked polysiloxane main chain as an adhesive matrix in a silicone-based fireproof sheet. Well-crosslinked polysiloxanes enable good thermal stability up to 350°C to ensure its thermal insulation performance below this temperature. The well-crosslinked polysiloxane main chain can be tuned to ceramicize preferably at a temperature above 350°C to produce an inorganic ceramic material that continues to bond the thermal insulation filler together, thereby providing excellent thermal insulation performance at a temperature above 350°C (e.g., 450°C, 650°C, 750°C, and even 950°C). In order to meet the mechanical strength requirements, the total polymer binder in the silicone-based fireproof sheet should be ≥57.5% by mass. In order to satisfy the thermal stability property, the silicone-based polymer in the total polymer binder should be ≥ 50 mass %, preferably ≥ 60 mass %, more preferably ≥ 70 mass %.

[0058] According to the present invention, a silicone-based fireproof sheet has a structure in which at least one thermal insulation filler selected from aerogel particles, hollow particles and mesoporous particles is bonded to a silicone-based polymer binder. The amount of the thermal insulation filler ranges from 5% to 40% by mass, 5% to 35% by mass, 5% to 30% by mass, 5% to 25% by mass, 5% to 20% by mass, 5% to 15% by mass, 5% to 10% by mass, 10% to 40% by mass, 10% to 35% by mass, 10% to 30% by mass, 10% to 25% by mass, 10% to 20% by mass, 10% to 15% by mass, 15% to 40% by mass, 15% to 35% by mass, 15% to 30% by mass, 15% to 25% by mass, 10% to 15% by mass, 15% to 40% by mass, 15% to 35% by mass, 15% to 30% by mass, 15% to 25% by mass, 10% to 15% by mass, 10% to 40% by mass, 10% to 35% by mass, 10 ...25% by mass, 10% to 15% by mass, 10% to 40% by mass % to 30 mass%, 20 mass% to 40 mass%, 20 mass% to 35 mass%, 20 mass% to 30 mass%, 20 mass% to 25 mass%, 25 mass% to 40 mass%, 25 mass% to 35 mass%, 25 mass% to 30 mass%, 30 mass% to 40 mass%, 30 mass% to 35 mass%, or 35 mass% to 40 mass%; and the amount of the cured silicone-based polymer adhesive ranges from 57.5 mass% to 95 mass%, 57.5 mass% to 90 mass%, 57.5 mass% to 85 mass%, 57.5 mass% to 80 mass% %, 57.5% to 75% by mass, 57.5% to 70% by mass, 57.5% to 65% by mass, 57.5% to 60% by mass, 60% to 95% by mass, 60% to 90% by mass, 60% to 85% by mass, 60% to 80% by mass, 60% to 75% by mass, 60% to 70% by mass, 60% to 65% by mass, 65% to 95% by mass, 65% to 90% by mass, 65% to 85% by mass, 65% to 80% by mass, 65% to 75% by mass, 65% to 70% by mass % to 95% by mass, 70% to 90% by mass, 70% to 85% by mass, 70% to 80% by mass, 70% to 75% by mass, 75% to 95% by mass, 75% to 90% by mass, 75% to 85% by mass, 75% to 80% by mass, 80% to 95% by mass, 80% to 90% by mass, 80% to 85% by mass, 85% to 95% by mass, 85% to 90% by mass, or 90% to 95% by mass, wherein the total mass of the solid content of the silicone-based fire retardant sheet is 100% by mass.

[0059] In the present invention, the thermal insulation filler includes at least one selected from aerogel particles, hollow particles and mesoporous particles. Specifically, the thermal insulation filler applied to the present invention may include but is not limited to aerogel powder, hollow glass beads, perlite, hollow ceramic beads, mesoporous particles, microporous particles, a mixture of mesoporous particles with different pore sizes ranging from 2nm to 50nm, and other inorganic fillers with a mesoporous structure or a hollow bubble structure. In some embodiments, the loading amount of the thermal insulation filler in the dry sheet is greater than 15% by mass, 15% to 30% by mass, 15% to 25% by mass, 15% to 20% by mass, 20% to 30% by mass, 20% to 25% by mass, or 25% to 30% by mass.

[0060] In the embodiments of the present disclosure, the average diameter or size of the thermal insulation filler ranges from 1 μm (=0.001 mm) to 1.20 mm, 10 μm (=0.01 mm) to 1.20 mm, 0.01 mm to 1.20 mm, 0.01 mm to 1.00 mm, 0.01 mm to 0.80 mm, 0.01 mm to 0.60 mm, 0.01 mm to 0.40 mm, 0.01 mm to 0.20 mm, 0.03 mm to 1.20 mm, 0.20 mm to 1.00 mm , 0.20mm to 0.80mm, 0.20mm to 0.60mm, 0.20mm to 0.40mm, 0.40mm to 1.20mm, 0.40mm to 1.00mm, 0.40mm to 0.80mm, 0.40mm to 0.60mm, 0.60mm to 1.20mm, 0.60mm to 1.00mm, 0.60mm to 0.80mm, 0.80mm to 1.20mm, 0.80mm to 1.00mm, or 1.00mm to 1.20mm.

[0061] In an embodiment of the present disclosure, aerogel particles, hollow particles and mesoporous particles having an average diameter or size ranging from 0.05 mm to 1.0 mm, 0.05 mm to 0.8 mm, 0.05 mm to 0.6 mm, 0.05 mm to 1.0 mm, or 0.05 mm to 0.8 mm are bonded in a silicone-based polymer adhesive cured by a condensation reaction. When the total mass of the solid content of the silicone-based fireproof sheet is 100 mass%, the preferred amount of the aerogel particles ranges from 15 mass% to 35 mass%, 15 mass% to 30 mass%, 15 mass% to 25 mass%, 15 mass% to 20 mass%.

[0062] In the present invention, the true density of aerogel particles, hollow particles and mesoporous particles may be less than 0.25 grams per cubic centimeter (g / cc), 0.001 g / cc to 0.25 g / cc, 0.05 g / cc to 0.20 g / cc, 0.05 g / cc to 0.15 g / cc, 0.05 g / cc to 0.10 g / cc, 0.10 g / cc to 0.25 g / cc, 0.10 g / cc to 0.20 g / cc, 0.10 g / cc to 0.15 ... and the thermal conductivity may be less than 0.1 W / mK, 0.01 W / mK to 0.1 W / mK, 0.01 W / mK to 0.06 W / mK, 0.01 W / mK to 0.03 W / mK, 0.03 W / mK to 0.1 W / mK, 0.03 W / mK to 0.0.6 W / mK, or 0.06 W / mK to 0.1 W / mK.

[0063] In the present invention, aerogel particles can be provided in any suitable form, such as granules, powders and beads. The chemical composition of the aerogel particles includes inorganic, organic, hybrid organic-inorganic compositions or any combination thereof. Any combination of the above forms and / or compositions can be used in the present invention. Optionally, the aerogel particles can be coated with one or more materials (such as polymers or elastomers), or treated with a treatment agent such as silane. A variety of different aerogel compositions can be used, including inorganic, organic and hybrid organic-inorganic compositions. Inorganic aerogels are generally based on metal oxide compounds, including but not limited to: silicon dioxide, titanium dioxide, zirconium oxide, aluminum oxide, hafnium dioxide, yttrium oxide, or based on various carbides, nitrides or any combination of the foregoing substances. Organic aerogels can be based on compounds including, but not limited to, urethanes, resorcinol formaldehyde, polyimides, polyacrylates, chitosan, polymethyl methacrylate, members of the acrylate oligomer family, trialkoxysilyl-terminated polydimethylsiloxanes, polyoxyalkylenes, polyurethanes, polybutylene diamines, members of the polyether material family, or combinations thereof. Examples of organic-inorganic hybrid aerogels include, but are not limited to, silica-PMMA, silica-chitosan, or combinations of the above organic and inorganic compounds. In some cases, organic polymers or organic-inorganic hybrid polymers can be thermally treated to produce carbon- or inorganic-based mesoporous or microporous materials, including aerogels.

[0064] The term "hollow particle" is understood to mean a particle having a dense or low porosity shell and a free space within the shell. The hollow particle according to the present invention has a shell whose thickness can be controlled. In the present invention, the hollow particle may include hollow glass particles and hollow ceramic beads.

[0065] In the present invention, the pore size of the mesoporous particles ranges from 2nm to 50nm, with a large specific surface area and a three-dimensional pore structure. According to the classification of chemical composition, mesoporous materials are generally divided into silicon-based and non-silicon-based mesoporous materials. Non-silicon-based mesoporous materials include transition metal oxides, phosphates and sulfides, such as silicoaluminophosphate (SAPO) formed after part of P in a molecular sieve material based on aluminophosphate is replaced by Si, and activated carbon with a large internal surface area and high pore capacity.

[0066] In the fireproof sheet based on silicone, the polymer adhesive based on silicone can be cured completely or partially via condensation reaction, for example, the polymer adhesive based on silicone or the semi-cured polymer adhesive based on silicone of fully cured.Or, the polymer adhesive based on silicone can be curable, water-based or solvent-based adhesive resin (that is, in non-cured state), which can be applied in sheet products.Or, the polymer adhesive based on silicone can be cured by the curing reaction initiated by hydrosilylation reaction or condensation reaction or free radical.In a preferred embodiment, the polymer adhesive based on silicone is cured.In a preferred embodiment, for environmentally friendly purposes, the polymer adhesive based on silicone is based on water (that is, water-containing).In a more preferred embodiment, the polymer adhesive based on silicone can further include colloidal silicon dioxide components.Most preferably, the polymer adhesive based on silicone can be cured by the condensation reaction of the silicone with hydrolyzable groups and the curing agent or other condensation reaction reagents for hydrolyzable silane.

[0067] Silicone-based polymer adhesives can be elastomeric or rigid, i.e., have a glass transition temperature above room temperature. Silicones are generally composed of four representative classes of structural units, namely M (R3SiO-), D (-OSiR2O-), T (RSiO 3 / 2 -) and Q(SiO 4 / 2 ), where R is a saturated or unsaturated alkyl or aryl group, and the subscript n / 2 means the number of oxygen atoms that are bridged and shared by two Si atoms. Silicone rubbers are mainly based on D structures, while resins are more heavily based on T structural units and Q structural units.

[0068] In embodiments of the present disclosure, at least 50 mass%, at least 55 mass%, at least 60 mass%, at least 65 mass%, or at least 70 mass% of the silicone-based polymer adhesive is a cured silicone product.

[0069] In an embodiment of the present disclosure, the polymer adhesive based on silicone is a silicone polymer adhesive resin based on water. In a preferred embodiment of the present disclosure, the polymer adhesive based on silicone comprises a silicone polymer adhesive based on water, and the silicone polymer adhesive based on water comprises colloidal silica by a condensation curing reaction using alkoxysilane as a crosslinking agent. Colloidal silica can be dispersed in water before mixing with a silicone polymer adhesive based on water, so that the weight ratio of colloidal silica (in terms of solid amount) to silicone polymer in the silicone emulsion is ≤0.5. Loading amount>0.5 may cause the rubber matrix to be too hard.

[0070] In an embodiment of the present disclosure, the silicone-based polymer adhesive further comprises at least one selected from the group consisting of: flame retardant additives, curing catalysts, silicone crosslinkers, rheology modifiers, defoaming additives, wetting additives, surface treatment agents, colorants, fillers other than the thermal insulation fillers, antioxidant additives, ultraviolet (UV) stabilizer additives, biocides, and adhesion promoter additives. In the present invention, the flame retardant additives include halogenated flame retardant additives and / or non-halogenated flame retardant additives, wherein examples of halogenated flame retardant additives include brominated flame retardant additives, such as brominated polymers or oligomers, brominated styrene-butadiene-styrene copolymers (e.g., FR-122P used in the embodiment), and preferably a combination of brominated flame retardant additives and antimony trioxide for forming a Br-Sb synergistic system; and examples of non-halogenated flame retardant additives may include ammonium polyphosphate, melamine polyphosphate, aluminum hydroxide, magnesium hydroxide, amorphous phosphorus, expandable graphite. In the present invention, the flame retardant additive can be dispersed or distributed throughout the silicone-based polymer binder (i.e., polymer matrix) in a loading range of 0% to 60% by mass of the dry sheet. A flame retardant additive with a loading of >60% by mass may result in insufficient thermal insulation performance required in battery fire protection applications. Rheology modifiers are used to tune the viscosity of the wet slurry, for example, in an amount of 0% to 2% by mass in the wet slurry. The silicone crosslinker may include TEOS (=tetraethoxysilane) or NPOS (=orthopropyl orthosilicate), in an amount of 0wt% to 5wt% in the wet slurry. Depending on the curing chemistry, the curing catalyst includes dioctyltin dilaurate or other. Defoaming additives are used to remove bubbles in the wet slurry, for example, in an amount of 0% to 5% by mass in the wet slurry. Wetting additives are used to wet the surface of hydrophobic fillers. Colorants or color masterbatches can impart the desired color to silicone-based fireproof sheets. Fillers other than the thermal insulation filler include, but are not limited to, silica, CaCO3 and hydromagnesite.

[0071] In the present invention, the aqueous silicone-based polymer adhesive may be curable, comprising: a polyorganosiloxane containing at least two hydroxyl groups or hydrolyzable groups bonded to silicon in each molecule. The molecular structure of the polyorganosiloxane may be linear, cyclic, branched, dendritic or reticular, but a linear or partially branched linear chain is preferred. The hydroxyl group or hydrolyzable group may be present at a terminal position on the molecular chain, or at a side chain position on the molecular chain, or at both positions. The hydrolyzable group may be exemplified by an alkoxy group, an alkoxyalkoxy group, an acetoxy group, an oxime group, an alkenyloxy group, an amino group, an aminooxy group and an amide group, wherein C 1-10 Alkoxy (e.g., methoxy, ethoxy, n-propoxy, isopropoxy, n-butoxy, tert-butoxy, hexyloxy, cyclohexyloxy, octyloxy, decyloxy, etc.) and C 2-10 Alkoxyalkoxy (eg, methoxymethoxy, methoxyethoxy, ethoxymethoxy, methoxypropoxy, etc.) is preferred.

[0072] Unsubstituted monovalent hydrocarbon groups and substituted monovalent hydrocarbon groups are examples of silicon-bonded organic groups other than hydroxyl groups or hydrolyzable groups. 1-10 Unsubstituted monovalent hydrocarbon groups are preferred for unsubstituted monovalent hydrocarbon groups. Unsubstituted monovalent hydrocarbon groups can be exemplified by C 1-10 Alkyl, such as methyl, ethyl, n-propyl, isopropyl, butyl, tert-butyl, hexyl, octyl, decyl, etc.; C 3-10 Cycloalkyl, such as cyclopentyl, cyclohexyl, etc.; C 2-10 Alkenyl, such as vinyl, allyl, 5-hexenyl, 9-decenyl, etc.; C 6-10 Aryl, such as phenyl, tolyl, xylyl, etc.; and C 7-10 Aralkyl, such as benzyl, methylbenzyl, phenethyl, etc. Among them, C 1-10 Alkyl, C 6-10 Aryl and C 2-10 Alkenyl, of which methyl and phenyl are particularly preferred.

[0073] The substituted monovalent hydrocarbon group can be exemplified by replacing one or more of the above unsubstituted monovalent hydrocarbon groups, especially C 1-10 The present invention also includes a group provided by all or part of the hydrogen atoms in the alkyl group and the phenyl group; an epoxy functional group such as a glycidyloxy group, an epoxycyclohexyl group, etc.; a methacrylic acid functional group such as a methacryloyloxy group, etc.; an acrylic acid functional group such as an acryloxy group, etc.; an amino functional group such as an amino group, an aminoethylamino group, a phenylamino group, a dibutylamino group, etc.; a sulfur-containing functional group such as a mercapto group, a tetrasulfide group, etc.; or a substituent group such as an alkoxy group, a hydroxycarbonyl group, an alkoxycarbonyl group, etc.

[0074] The following are specific examples of substituted monovalent hydrocarbon groups: 3,3,3-trifluoropropyl, perfluorobutylethyl, perfluorooctylethyl, 3-chloropropyl, 3-glycidoxypropyl, 2-(3,4-epoxycyclohexyl)ethyl, 5,6-epoxyhexyl, 9,10-epoxydecyl, 3-methacryloxypropyl, 3-acryloxypropyl, 1,1-methacryloxyundecyl, 3-aminopropyl, N-(2-aminoethyl)aminopropyl, 3-(N-phenylamino)propyl, 3-dibutylaminopropyl, 3-mercaptopropyl, 3-hydroxycarbonylpropyl, methoxypropyl and ethoxypropyl.

[0075] The viscosity of the silicone-based polymer adhesive at 25° C. is not particularly limited; however, considering the strength of the cured sheet of the present invention and the handling characteristics during its production, the viscosity of the silicone-based polymer adhesive at 25° C. is preferably 50 mPa·s to 2,000,000 mPa·s, more preferably 100 mPa·s to 500,000 mPa·s, and even more preferably 500 mPa·s to 100,000 mPa·s.

[0076] The silicone-based polymer binder may be a diorganopolysiloxane terminated with hydroxyl groups at both molecular chain ends. Such a diorganopolysiloxane terminated with hydroxyl groups at both molecular chain ends may be exemplified by a diorganopolysiloxane having a general formula of HO(R2SiO): m A polyorganosiloxane represented by wherein H represents the same silicon-bonded unsubstituted and substituted monovalent hydrocarbon groups other than the hydroxyl or hydrolyzable groups described above, wherein C 1-10 Alkyl, C 6-10 Aryl and C 2-10 Alkenyl is preferred, and methyl and phenyl are particularly preferred. The subscript m is an integer having a value of at least 2, and is preferably a number providing a viscosity of 50 mPa·s to 2,000,000 mPa·s at 25°C.

[0077] In the present invention, preferably aqueous silicone-based polymer adhesives that can be cured by condensation reaction are commercially available. For example, DOWSIL TM 8005 water-based resin, DOWSIL TM 8004 water-based resin, Dowsil TM IE-2404 is commercially available from DOW SILICONES CORPORATION or its affiliates. Such curable silicone-based polymer adhesives or mixtures thereof can be cured by removing water under heating to 140°C.

[0078] In the present invention, the adhesive used can be a mixture of a curable silicone-based polymer adhesive and other organic polymer adhesive resin / rubber composition. In an embodiment of the present invention, the other organic polymer adhesive resin / rubber composition includes but is not limited to polyurethane adhesive, polyacrylate / polyacrylic acid adhesive, epoxy resin adhesive, phenolic resin adhesive, polyamide adhesive, polyester adhesive, polyolefin adhesive, polystyrene adhesive and ethylene-vinyl acetate copolymer. In a preferred embodiment, the amount of the curable silicone-based polymer adhesive is at least 50% by mass, at least 55% by mass, at least 60% by mass, at least 65% by mass, at least 70% by mass, at least 75% by mass, at least 80% by mass, at least 85% by mass of the mixture. Specifically, the aqueous mixture of the silicone-based polymer adhesive and the polyurethane adhesive is preferably used in the present invention, and the mixture of the aqueous adhesive resin can be cured by removing water under heating to 140°C.

[0079] In the present invention, the water-curable silicone-based composition can form the silicone-based fire-proof sheet through a curing reaction, and the water-curable silicone-based composition comprises:

[0080] (A) a curable silicone-based polymer adhesive containing at least 50 mass %, at least 55 mass %, at least 60 mass %, at least 65 mass % or at least 70 mass % of a curable silicone polymer, wherein the curable silicone-based polymer adhesive ranges from 57.5 mass % to 95 mass %,

[0081] 57.5% to 90% by mass, 57.5% to 85% by mass, 57.5% to 80% by mass, 57.5% to 75% by mass, 57.5% to 70% by mass, 57.5% to 65% by mass, 57.5% to 60% by mass, 60% to 95% by mass,

[0082] 60% to 90% by mass, 60% to 85% by mass, 60% to 80% by mass, 60% to 75% by mass, 60% to 70% by mass, 60% to 65% by mass, 65% to 95% by mass, 65% to 90% by mass, 65% to 90% by mass

[0083] % to 85% by mass, 65% to 80% by mass, 65% to 75% by mass, 65% to 70% by mass, 70% to 95% by mass, 70% to 90% by mass,

[0084] 70% to 85% by mass, 70% to 80% by mass, 70% to 75% by mass, 75% to 95% by mass, 75% to 90% by mass, 75% to 85% by mass, 75% to 80% by mass, 80% to 95% by mass, 80% by mass

[0085] % to 90% by mass, 80% to 85% by mass, 85% to 95% by mass, 85% to 90% by mass, or 90% to 95% by mass;

[0086] (B) at least one thermally insulating filler selected from hollow particles including mesoporous particles (such as aerogels) and / or microporous particles, the at least one thermally insulating filler being present in an amount ranging from 5% to 40% by mass, from 5% to 35% by mass, from 5% to 30% by mass, from 5% to 25% by mass, from 5% to 20% by mass, from 5% to 15% by mass, from 5% to 10% by mass, from 10% to 40% by mass, from 10% to 35% by mass, from 10% to 30% by mass, from 10% to 15% by mass

[0087] to 25 mass %, 10 mass % to 20 mass %, 10 mass % to 15 mass %, 15 mass % to 40 mass %, 15 mass % to 35 mass %, 15 mass % to 30 mass %,

[0088] 15% to 25% by mass, 15% to 20% by mass, 20% to 40% by mass, 20% to 35% by mass, 20% to 30% by mass, 20% to 25% by mass, 25% to 40% by mass, 25% to 35% by mass, 25% by mass

[0089] % to 30% by mass, 30% to 40% by mass, 30% to 35% by mass, or 35% to 40% by mass;

[0090] (C) a curing agent of component (A),

[0091] (D) water, and optionally

[0092] (E) when the total mass of the solid content of the silicone-based fireproof sheet is 100 mass%, at least one selected from the group consisting of: a flame retardant additive, a curing catalyst, a rheology modifier, a defoaming additive, a wetting additive, a surface treatment agent, a colorant, a filler other than the thermal insulation filler, an antioxidant additive, an ultraviolet (UV) stabilizer additive, a biocide, and an adhesion promoter additive.

[0093] In an embodiment of the present disclosure, component (A) is a silicone-based polymer adhesive containing curable silicone and other curable polymerizable materials, wherein the amount of the other curable polymerizable materials is 0% to 30% by mass, 10% to 30% by mass, 20% to 30% by mass, 0% to 20% by mass, 0% to 10% by mass, 20% to 30% by mass, 10% to 20% by mass based on the total mass of the silicone-based polymer adhesive. Component (A) of the silicone-based polymer adhesive may be first emulsified or uniformly dispersed in (D) water before mixing.

[0094] As the (C) curing agent of the component (A), crosslinkable silane or condensation curing agent is exemplified. Typically, hydrolyzable silane (such as TEOS (tetraethoxysilane), MTMS (methyltrimethoxysilane), NPOS (n-propyl orthosilicate) and mixtures thereof) is preferably used as the component (C).

[0095] In the present invention, the method for producing the silicone-based fireproof sheet comprises:

[0096] (1) mixing a silicone-based polymer binder emulsion with a thermal insulation filler in an aqueous solution to form a wet slurry or paste;

[0097] (2) applying the wet slurry or paste to a substrate (e.g., release paper), wherein the thickness of the layer of the wet slurry or paste is in the range of 0.2 mm to 10 mm, 0.2 mm to 5 mm, or 2 mm to 10 mm (in the present invention, a thickness <0.2 mm may make it easier to generate pinholes on the wet film; and a thickness >10 mm may make it difficult to remove water and form a crack-free dry sheet;

[0098] (3) Water is removed by subjecting the wet film to temperatures up to 140°C and air circulation to form a dry sheet, wherein temperatures exceeding 140°C may cause cracks and other defects in the sheet.

[0099] In an embodiment of the present invention, the method for producing the silicone-based fire-resistant sheet may further include: adding one or more ingredients selected from colloidal silica, cross-linking agents, catalysts, rheology modifiers, defoaming additives, wetting additives, colorants, other fillers, biocides, antioxidant additives and UV stabilizers to the silicone-based polymer adhesive emulsion before mixing with the thermal insulation filler in an aqueous solution.

[0100] In an embodiment of the present invention, the method for producing the silicone-based fire-resistant sheet may further include: after adding the thermal insulation filler to the silicone-based polymer adhesive emulsion, adding one or more ingredients selected from colloidal silica, cross-linking agents, catalysts, rheology modifiers, defoaming additives, wetting additives, colorants, other fillers, biocides, antioxidant additives and UV stabilizers to the wet slurry or paste.

[0101] In an embodiment of the present invention, the method for producing the silicone-based fireproof sheet may further include: adding a certain amount of water to the wet slurry or paste to tune the fluidity of the wet slurry or paste. The amount of water to be added is to ensure a slightly good fluidity of the uniform slurry for coating. Depending on the solid content of the emulsion and the loading of the filler, if the fluidity of the slurry is sufficient to be coated into a specific wet film thickness, it may not be necessary to add water. If the filler loading exceeds a specific volume concentration, the slurry is not flowable, so it is difficult to coat the slurry into a wet film with a uniform thickness, and water is added to improve fluidity. In some cases, a thickener loading is added accordingly to achieve a specific viscosity. On the other hand, due to several problems that occur at the same time, adding too much water should be avoided. One problem is the waste of energy consumption to dry excess water. The second problem is the increase in the volume concentration of porous pores and channels left in the final mat due to water evaporation, which may deteriorate thermal insulation performance. The third problem is the additional amount of thickener required to maintain the viscosity of the slurry. This amount of thickener remains in the final mat and may have a negative impact on mechanical properties.

[0102] In an embodiment of the present invention, the method for producing the silicone-based fireproof sheet may further include: coating a second layer of wet slurry or paste on top of the dried layer obtained by the above step (3), and then further drying. If necessary, the method may further include coating a third layer of wet slurry or paste on the dried second layer. Optionally, the method of the present invention may repeat the coating and drying steps several times.

[0103] In an embodiment of the present invention, the method of producing the silicone-based fire-proof sheet may further include: removing the dry sheet from a substrate such as a release paper.

[0104] In the present invention, a silicone-based fireproof sheet containing 5wt.% to 40wt.% of aerogel particles, hollow particles and mesoporous particles and ≥57.5wt.% of a polymer binder (which can be a single silicone or a mixture of silicone and an organic polymer) can be used in a secondary battery pack including at least one battery module housing, wherein the housing includes a plurality of battery cells electrically connected to each other. The preferred shape of the battery cell is prismatic or pouch-shaped, and the battery cell is preferably protected by the silicone-based fireproof sheet.

[0105] In an embodiment of the present invention, a battery pack structure is described, in which the silicone-based fireproof sheet is completely or partially arranged in the space between at least two adjacent individual battery cells. When preparing the battery pack structure, the silicone-based fireproof sheet can be cured by removing water before arranging it in the space between at least two adjacent individual battery cells. In this production method of the battery pack structure, the "cured" or "semi-cured" silicone-based fireproof sheet can be completely or partially arranged (including inserted) in the space between at least two adjacent individual battery cells to prevent heat transfer from the hot surface of the "fired" cell due to the thermal runaway of the "fired" cell propagating to the adjacent good cells.

[0106] Moreover, the silicone-based fireproof sheet can be arranged in the space between at least two adjacent individual battery cells by removing the water of the curable silicone-based composition in the space via a curing reaction. In this embodiment of the present invention, a battery pack structure is prepared using a curable silicone-based composition, which can be cured into the silicone-based fireproof sheet. More specifically, this production method of the battery pack structure includes the following steps: step (BI): a step of completely or partially filling the space between at least two adjacent individual battery cells with the aqueous curable silicone-based composition as a wet slurry layer; and step (B-II): after step (BI), a step of forming a silicone-based fireproof sheet in the space between at least two adjacent individual battery cells by removing water from the aqueous curable silicone-based composition at a temperature of up to 140°C.

[0107] Any of the production methods may be employed to arrange the silicone-based fireproof sheet into the space between at least two adjacent individual battery cells, taking into account its process requirements during battery assembly or the required fireproof performance of the battery pack structure.

[0108] The silicone-based fireproof sheet partially or completely fills the open space of the battery module housing and / or partially or completely covers the battery cell, and / or partially or completely covers the module housing, and optionally covers the cover of the battery module housing. The silicone-based fireproof sheet is obtained by dispersing the heat-insulating filler into a polymer binder emulsion, applying it to a specific wet thickness, and forming the final sheet with a heat-insulating inorganic filler after drying the water. The heat-insulating inorganic filler has a mesoporous structure or a hollow structure, and the true density is less than 0.25g / cc. The silicone-based fireproof sheet can also be assembled between the water-cooled plate and the metal plate of the battery housing to prevent heat diffusion between the water-cooled plate and the metal plate of the battery housing. The silicone-based fireproof sheet is obtained by dispersing the heat-insulating filler into a polymer binder emulsion, applying it to a specific wet thickness, and forming the final sheet with a heat-insulating inorganic filler after drying the water. The heat-insulating inorganic filler has a mesoporous structure or a hollow structure, and the true density is less than 0.25g / cc. It can be manufactured in advance and then assembled into the battery case. It can also be manufactured by applying a slurry obtained by dispersing a thermal insulation filler in a polymer binder emulsion to the inner face of a metal plate of the battery case and forming a thermal insulation coating sheet after drying off the water.

[0109] Example

[0110] Some embodiments of the present invention will now be described in the following examples, in which all parts and percentages are by weight unless otherwise specified.

[0111] The information of the raw materials used in the examples is listed in Table 1 below:

[0112] Table 1. Raw materials used in the examples

[0113]

[0114]

[0115] Inventive Examples 1 to 5 (IE 1 to IE 5) and Comparative Examples 1 to 3 (CE 1 to CE 3)

[0116] In Inventive Examples 1 to 5 of the present disclosure, silicone-based fireproof sheets were produced using those raw materials and their amounts described in Table 2. Comparative Examples 1 to 3 are provided herein as controls.

[0117] Table 2: Formulations used in the examples

[0118]

[0119] For IE1 to IE4 and CE1 to CE3, they involve three steps:

[0120] Step 1: preparing wet slurry;

[0121] Step 2: applying the wet slurry to a substrate and removing the water to provide a dry sheet; and

[0122] Step 3: Test the thermal insulation properties of the dried sheets at elevated temperatures.

[0123] A detailed description of these steps is provided below:

[0124] Step 1: Prepare wet slurry

[0125] Dowsil 8005, deionized water (if necessary), FR-122P (if necessary), and Sb2O3 (if necessary) were added to a 1 liter plastic cup and mixed with a Cowles paddle at a stirring speed of 300 rpm to form a uniform slurry. Keltrol CG powder was then slowly added under stirring at 300 rpm to ensure powder dissolution and avoid agglomeration of Keltrol CG powder. After its complete dissolution and viscosity increase, IC3110 or S-15 (if necessary) was gradually added under stirring at 300 rpm to prepare a uniform slurry.

[0126] Step 2: Apply the wet slurry to the substrate and remove the water to provide a dry sheet

[0127] The slurry obtained in step 1 was coated on a PTFE sheet with a doctor blade to form a wet sheet having a thickness of 2.5 mm. The wet sheet was dried in an oven at 90° C. for 1 hour to obtain a dried sheet.

[0128] Step 3: Thermal insulation properties of the sheet at high temperatures.

[0129] The dried sheets were cut into 8 cm x 8 cm squares, placed on a heating stage stabilized at 630°C, and mounted to an Al plate with an outer diameter (OD) of 0.5 mm partially embedded in a 0.4 mm groove with two K-type thermocouples, which were in close contact with the back surface of the specimen to record the back temperature. All surfaces of the Al plate were well covered with thermal insulating asbestos sheets to control thermal diffusion. A steel load was further mounted on the Al plate to produce a pressure of 0.03 MPa on the specimen. A description of the setup is provided in Figure 1. All installations were completed within 10 seconds from the time the specimen was attached to the heating stage. The heating stage temperature of 630°C was calibrated by mounting a square 8cm×8cm aerogel sheet / pad with a thickness of 4±0.2mm on an Al plate, with a thermocouple on the center of the sheet in direct contact with the heating stage surface. The calibration lasted for at least 20min for a stable 630°C heating stage surface before starting the thermal insulation performance test. In the test, the back temperature was recorded from the time the specimen was attached to the heating stage. The test lasted 20min. The original thickness of the sheet specimen was measured at the four corners, and the average thickness was calculated. During the test, a feeler gauge was inserted between the heating stage and the Al plate to measure the thickness just before the end of the test. Record the back temperature changes and thickness changes over the test duration.

[0130] For IE5, it still involves the above three steps, but step 2 is split into two parts:

[0131] 2-1: Apply the wet slurry to the substrate and remove the water to obtain a dry loose sheet;

[0132] 2-2: Dowsil 8005 (ie, polymer emulsion) was impregnated into the dried loose sheet and water was removed to obtain a final sheet.

[0133] The details of step 2-1 and step 2-2 are as follows:

[0134] Step 2-1:

[0135] A slurry of a mixture of Synsegra YS-3000, water, Keltrol CG thickener, defoamer 4-88 and aerogel filler IC3110 was coated on a PTFE sheet with a doctor blade to form a wet sheet with a thickness of 2.5 mm. The wet sheet was dried in an oven at 90° C. for 1 hour to obtain a dry loose sheet.

[0136] Step 2-2:

[0137] Dowsil 8005 was evenly impregnated into the loose sheet by brushing. The impregnated loose sheet was placed in an oven at 90°C for 1 hour to obtain a dry sheet.

[0138] Table 3: Mass % and mass % of fillers in Examples 1 to 5 (IE1 to IE5) of the present invention and Comparative Examples 1 to 3 (CE1 to CE3) Volume %, and thermal insulation performance test results

[0139]

[0140] The total binder mass % in the dry sheet is critical for mechanical strength. CE3 showed unacceptable dry sheet strength and was easily ground into powder with fingers because the binder loading in CE3 was below 60%. IE3 showed edge sheet strength with 60.2 mass % binder, indicating that >60 mass % binder is required in the dry sheet to ensure adequate sheet strength for downstream assembly operations in battery module and pack production.

[0141] Compared to CE1 (i.e. silicone sheet without any thermal insulating filler), IE1 to IE5 show much lower back temperatures (see Figures 2 to 4 ), indicating significantly improved thermal insulation performance. In order to meet the acceptance criteria in practical design, for a thermal insulation sheet with a thickness of 2.5 mm, a lower back temperature of less than 220°C, preferably less than 170°C, is required when placed on a heating table at 630°C and 0.03 MPa pressure for 20 min. All embodiments of the present invention meet the criteria in practical design. The amount of thermal insulation filler in IE1 is close to the bottom line, indicating that >15wt% thermal insulation filler is preferred to maintain good thermal protection performance.

[0142] The weight % of polysiloxane in the adhesive is critical for thermal insulation performance. CE2 shows that using polyurethane as the main adhesive, the thermal insulation performance is even worse than CE1 (i.e., silicone sheet without any thermal insulation filler). Ie5 shows that when polysiloxane is the majority of the adhesive, the thermal insulation performance is good. It is recommended that the mass % of polysiloxane in the adhesive should be >50%, preferably >60%, and more preferably >70%.

[0143] All examples except IE4 did not cause any fire during the test due to the addition of flame retardant additives in the sheets. IE4 caused a small fire but it was quickly extinguished when it was removed from the heating table at the end of the test. This small fire can usually be extinguished by adding some flame retardant additives.

[0144] Testing and Evaluation

[0145] Acceptance criteria consist of three parts: mechanical strength, thermal insulation at elevated temperatures, and flame ignition during hot table testing.

[0146] Mechanical strength

[0147] The mechanical strength of the thermal insulation sheet was evaluated by bending. If a sheet with a thickness of 2.5 mm can be bent more than 50 times with a radius of 1 cm from one end to the other without any change or damage, the sheet is rated as "very good". If the sheet can be bent more than 10 times without obvious damage, the sheet is rated as "good". If the sheet can be bent more than 1 time without obvious damage, the sheet is rated as "marginal". If the sheet cannot be bent, the sheet is rated as "unacceptable". Since the sheets are rolled up in mass production, at least one bending is required. The mechanical strength of the sheets in CE3 and IE3 is recommended, indicating that an adhesive loading of >60 mass% is required.

[0148] Thermal insulation at high temperatures

[0149] Thermal insulation at high temperatures was evaluated by a heating table test. In practical design, for a thermal insulation sheet with a thickness of 2.5 mm, a back temperature of less than 220°C is required when placed on a heating table at 630°C and 0.03 MPa pressure for 20 min. All embodiments of the present invention meet the criteria. IE1 is close to the bottom line, indicating that >15% by mass of thermal insulation filler is preferred to maintain good thermal protection performance. On the other hand, CE1 and IE5 show that the mass % of polysiloxane in the adhesive should be dominant to ensure sufficient thermal insulation performance. The mass % of polysiloxane in the adhesive should be >50%, preferably >60%, more preferably >70%.

[0150] Flame ignition during hot stage testing

[0151] The flame ignition of thermal insulation sheets is evaluated by the appearance of fire during the test. If the sheet is set on fire, additional heat may be generated, which should be avoided. IE1 to IE3 show that flame ignition can be avoided by adding flame retardant additives.

Claims

1. A silicone-based fireproof sheet, the silicone-based fireproof sheet having a structure in which at least one thermal insulation filler selected from aerogel particles, hollow particles and mesoporous particles is bonded to a silicone-based polymer binder, wherein when the total mass of the solid content of the silicone-based fireproof sheet is 100 mass%, the amount of the thermal insulation filler ranges from 5 mass% to 40 mass%, and the amount of the silicone-based polymer binder ranges from 57.5 mass% to 95 mass%. 2 . The silicone-based fireproof sheet according to claim 1 , wherein the average size of the thermal insulation filler is 1 μm to 1.20 mm, and at least 50% by mass of the silicone-based polymer binder is cured silicone.

3. The silicone-based fire-proof sheet according to claim 1, wherein when the total mass of the solid content of the silicone-based fire-proof sheet is 100 mass%, the average size of the aerogel particles ranges from 0.01 mm to 1.0 mm, and the amount of the aerogel particles ranges from 15 mass% to 35 mass%. 4 . The silicone-based fire-proof sheet according to claim 1 , wherein the silicone-based polymer adhesive is a water-based silicone polymer adhesive. 5 . The silicone-based fire-proof sheet according to claim 1 , wherein the silicone-based polymer binder contains a water-based silicone polymer binder including colloidal silica.

6. The silicone-based fire-proof sheet according to claim 1, wherein the silicone-based polymer binder further comprises at least one selected from the group consisting of: a flame retardant additive, a curing catalyst, a rheology modifier, a defoaming additive, a wetting additive, a surface treatment agent, a colorant, a filler different from the thermal insulation filler, an antioxidant additive, a biocide, an ultraviolet (UV) stabilizer additive, and an adhesion promoter additive. 7 . The silicone-based fireproof sheet according to any one of claims 1 to 6 , which is applied to a battery pack.

8. A battery pack structure, wherein the silicone-based fire-proof sheet according to any one of claims 1 to 6 is arranged entirely or partially into a space between at least two adjacent individual battery cells.

9. The battery pack structure according to claim 8, wherein the shape of the battery is a prismatic shape or a pouch shape. 10 . The battery pack structure according to claim 8 , wherein the silicone-based fireproof sheet is a silicone-based sheet that is cured before being arranged in the space between at least two adjacent individual battery cells.

11. The battery pack structure according to claim 8, wherein the silicone-based fire-proof sheet is a silicone-based product cured by a curing reaction of a curable silicone-based composition in the space between at least two adjacent individual battery cells.

12. An aqueous curable silicone-based composition, which forms the silicone-based fire-proof sheet according to any one of claims 1 to 7 through a curing reaction, the aqueous curable silicone-based composition comprising: (A) a silicone-based polymer adhesive containing at least 50% by mass of a curable silicone polymer, the amount of the silicone-based polymer adhesive ranging from 57.5% by mass to 95% by mass, (B) at least one thermally insulating filler selected from aerogel particles, hollow particles and mesoporous particles, the amount of the at least one thermally insulating filler ranging from 5% to 40% by mass, (C) a curing agent, (D) water, and optionally (E) when the total mass of the solid content of the silicone-based fire-proof sheet is 100 mass%, at least one selected from the group consisting of: a flame retardant additive, a curing catalyst, a rheology modifier, a defoaming additive, a wetting additive, a surface treatment agent, a colorant, a filler different from the thermal insulation filler, an antioxidant additive, a biocide, an ultraviolet (UV) stabilizer additive, and an adhesion promoter additive.

13. The aqueous curable silicone-based composition according to claim 12, wherein component (A) is a silicone-based polymer binder containing a curable silicone polymer and other curable / polymerizable materials, wherein the amount of the other curable / polymerizable materials is 0% to 30% by mass.

14. The aqueous curable silicone-based composition according to claim 12, wherein component (A) is emulsified or uniformly dispersed in (D) water.

15. A method for producing a silicone-based fireproof sheet according to any one of claims 1 to 7, the method comprising the following steps: Step (I): a step of applying the aqueous curable silicone-based composition according to any one of claims 11 to 13 as a wet slurry layer onto a substrate optionally having a release layer, and Step (II): a step of forming the silicone-based fire-proof sheet by removing water from the applied aqueous curable silicone-based composition at a temperature of up to 140° C. after step (I).

16. The method for producing a silicone-based fireproof sheet according to claim 15, wherein in step (I), the thickness of the wet slurry layer of the aqueous curable silicone-based composition is 0.2 mm to 10.0 mm.

17. The method for producing a silicone-based fire-proof sheet according to claim 15, further comprising the step of controlling the viscosity and / or fluidity of the aqueous curable silicone-based composition by adding water and / or a rheology modifier before or simultaneously with step (I).

18. A method of producing a battery pack structure according to claim 8, the method comprising the step of arranging the silicone-based fireproof sheet according to any one of claims 1 to 7 entirely or partially in a space between at least two adjacent individual battery cells.

19. A method for producing a battery structure according to claim 8, the method comprising the following steps: Step (BI): a step of completely or partially filling the space between at least two adjacent individual battery cells with the aqueous curable silicone-based composition according to any one of claims 12 to 14 as a wet slurry layer, and Step (B-II): After step (BI), a step of forming a silicone-based fire-retardant sheet in the space between at least two adjacent individual battery cells by removing water from the coated aqueous curable silicone-based composition at a temperature up to 140°C.

Citation Information

Patent Citations

  • Energy-saving thermal insulation material and preparation method thereof

    CN108793932A

  • Secondary battery pack with improved thermal management

    US10501597B2

  • Aerogel-based material that is super-insulating at atmospheric pressure

    US10604642B2

  • Aerogel-based vehicle thermal management systems and methods

    US20070238008A1